Pro PowerShell Desired State Configuration An In-Depth Guide to Windows PowerShell DSC - Chaganti, Ravikanth (Apress, 2018)
Use Windows PowerShell Desired State Configuration (DSC) and DSC Core to configure your infrastructure on-premises and in the cloud. In an environment where changes and deployments are happening all the time, DSC makes the necessary adjustments to the system so you don't have to. Pro Desired State Configuration shows you how. PowerShell Desired State Configuration (DSC) is a powerful configuration management platform that makes it easier than ever to perform configuration management of your infrastructure, whether on-premises or in the cloud. With Pro PowerShell Desired State Configuration, Ravikanth Chaganti revises and significantly expands his previous edition, bringing you a complete in-depth reference for applying this evolving technology in your day-to-day work. What's new in this edition? Get up-to-date, in-depth guidance on DSC in the data center Understand the central role that DSC plays in DevOps today Understand how DSC can be integrated into build and release management tools Learn to think and act like a developer when automating your configuration management, creating a testable, robust process that you can use again and again Find out why and how DSC has an important role to play in public and private cloud deployments Apply DSC in the cloud with Microsoft Azure or Amazon Web Services or Google Cloud Platform.